К ВОПРОСАМ ИСТОРИИ И ЭТНОГРАФИЧЕСКИХ ОСОБЕННОСТЕЙ АЗЕРБАЙДЖАНСКОГО КОВРА. - Алиев, С. (Journal of Oriental Studies, 2016)
Автор мақалада Әзірбайжан кілемінің этнография-лық ерекшеліктері мен тарихы туралы мәселелерінетоқталады.The article is devoted to development way of theAzerbaijan carpet weaving and ethnographic characteristicsof the Azerbaijan carpet. The Article also analyses thespecifics of the Azerbaijan carpets on regions under thesources and ethnographic materials, provides informationabout individual carpet schools and the role and place ofcarpets in the home and the culture of the people areprovided.